The Oregon Trail [large type] - Johnstone, William W.; Johnstone, J. A. (Go West Young Man, 2024)
"Wagon Master Clayton Scofield has led countless families across the dusty, wide-open territories of the West, helping the brave, sometimes reckless pioneers settle into new lives brimming with the promise of good lives. Accompanied by his nephew Clint Buchanan riding as scout and cook Spud Williams, Scofield's latest trail finds him guiding a train of thirty wagons from Independence, Missouri, to the distant dream of Oregon. It isn't long before the pioneers fall prey to the hazards of the countryside-both natural and man-made. The rough currents of the Kansas River tears a family apart. A fur trapper threatens Scofield in a foolhardy attempt to win the affections of an uninterested lady. Kill crazy Lakota Sioux warriors attack wagon train and slaughter without mercy. Scofield can't remember the trail ride ever being this treacherous and unforgiving-and he knows there's even worse things awaiting them along the far-reaching miles before they reach their destination."--